Prevalence of Metabolic Syndrome in Post Menopausal Females (An Observational Study) - Navneet Kaur; Parneet Kaur; Sanjeev Kumar; Preetkanwal Sibia; Avneet Kaur (GMC Patiala Journal of Research and Medical Education, 2020)
Menopause is defined as permanent cessation of menstruation following the loss of ovarian activity. Metabolic syndrome is cluster of metabolic abnormalities characterised by abdominal obesity, hyperglycaemia, decreased high density lipoprotein, increased triglycerides and high blood pressure, which predispose the individual for both cardiovascular diseases and type 2 diabetes. Some studies have shown a causal relationship between menopause and the risk that compose the metabolic syndrome, while others attribute the increase in risk only to the aging process. Aims & Objectives: Thus, this study was done to determine the prevalence of metabolic syndrome in postmenopausal female. Material & Methods: The present study was done in postmenopausal females presenting in menopause clinic at Govt. Medical College and Rajindra Hospital, Patiala for a period of one year from January 2017 to December 2017. The parameters of metabolic syndrome were assessed according to Modified ATP lll (2005) criteria. Results: A total of 190 postmenopausal females were enrolled during study period. The mean age of the study subjects was 59.88±7.99years. It was observed that mean values of all components of metabolic syndrome in our study population were above the cut off levels given by Modified ATPIII Criteria. This corroborates the high prevalence of all components of metabolic syndrome in our study. In study subjects, blood pressure (87.89%) presented the highest prevalence followed by elevated waist circumference (68.95%), elevated fasting blood sugar or DM (62.10%), elevated triglycerides (49.47%) and low HDL (41.05%). The prevalence of metabolic syndrome among our study subjects was 67.89%. Conclusion: The prevalence of MS is very high in this part of India, and this can be attributed to the higher prevalence of hypertension& obesity in the people in North India. There is an urgent need to establish magnitude of the problem and incorporate management prevention strategies within the existing health infrastructure.